ANALYSIS OF THE HALALITY CRITICAL POINT OF GOAT MILK YOGURT AND DATE (Phoenix dactylifera) EXTRACT FORTIFICATED WITH ZINC - MUHAMMAD FAIS BAIDHOWI; Endah Budi Permana Putri (Journal of Halal Research, Policy, and Industry, 2024)
Halal is one of the requirements for products to enter the global market, one of which is Indonesia. Law No. 23 of 2014 concerning halal product guarantees has a mandate, namely regarding the demand for the government to form a Halal Product Guarantee Organizing Agency. This study aims to determine the critical point of halal goat milk yogurt and zinc-fortified date extract.The design used in this study is descriptive research with a literature study method. This study uses observation sheets and stationery which are useful for writing down the results of observations at the research location. The materials used in making zinc-fortified goat milk yogurt are fresh goat milk, Lactobacillus bulgaricus and Streptococus thermopillus bacteria, zinc sulfate monohydrate, and ajwa date extract. Critical Points of Halal Goat Milk Yogurt and Zinc Fortified Date Extract in terms of ingredients are Lactobacillus bulgaricus and Streptococcus thermopillus bacteria, Zinc Sulfate Monohydrate and Ajwa Date Extract while in terms of process is during the fermentation of yogurt at a temperature of 37 C for 24 hours. Suggestions that can be taken from the study are that it is hoped that further researchers can dig deeper by using more journals or previous studies in order to get more detailed results related to this descriptive study, while the general public and producers can pay attention again to the composition and process of the product.